(untitled) (Indian Journal of Arid Horticulture, 2025)
Garlic is an important commercial spice crop of India. It is the second most important widely used and cultivated bulb crops after onion. Garlic bulb are rich source of carbohydrates, protein, phosphorus, vitamin C and also have several medicinal values. The productivity of garlic in India is low (4.07 t ha’) in comparison to other countries. Thus, there is an ample scope for increasing productivity and production thorough fertilizers in particular to biofertilizers in light textured soils. The present experiment was conducted to study the effect of biofertilizers on growth and yield of garlic.